Infection rates in surgical procedures: a comparison of cefalexin vs. a placebo - Daude-Lagravei, A.; Carozzo, C.; Fayolle, P.; Yiguier, E.; Viateau, Y.; Moissonnier, P. (Veterinary and Comparative Orthopaedics and Traumatology, 2001)
The aim of this study was to evaluate the efficacy of antibiotic prophylaxis in small animal surgery. Three hundred and twenty-nine dogs and 544 cats were included in a prospective, randomised, blind trial to determine the frequency of wound infection after clean and cleancontaminated surgical procedures. The animals were allocated to one of two groups: group A received a placebo and group B received cefalexin. The infection rate was measured in each group and correlated with different criteria (age, duration and type of the operation, anaesthetic and Altemeier’s class, surgeon’s experience). Globally, seventyeight cases of infection were noted (8.9%). The infection rates in the two groups were not significantly different (9.4% in group A and 8.5% in group B). Infection rate was not affected by the different criteria studied. However, the percentage of animals infected in group B tended to be lower than that of group A as the surgeons’ experience increased.The results of a study to evaluate the efficacy of the prophylactic use of antibiotics are described. The infection rates in animals that received the placebo and in those that received cefalexin were not significantly different (9.4% vs. 8.5%, p <0.05, respectively). We conclude that the antibiotic prophylaxis is not recommended for clean and clean-contaminated surgical procedures.
Keywords: Antibiotic prophylaxis; surgery; infection; cephalexin